Principles of small business - Barrow, Colin; Brown, Robert (London : International Thomson Bussiness Press, 1997)
The difficulties of getting into business; The difficulties of staying in business; and Difficulties in deciding whether to reinvest or to sell the business.
Keywords: Business; Management; Small business; Small business; Small business -- Management